Unraveling biochar surface area on structure and heavy metal removal performances of carbothermal reduced nanoscale zero-valent iron - Tharindu N. Karunaratne; Prashan M. Rodrigo; Daniel O. Oguntuyi; Todd E. Mlsna; Jilei Zhang; Xuefeng Zhang (Journal of Bioresources and Bioproducts, 2023)
Carbothermal reduction using biochar (BC) is a green and effective method of synthesizing BC-supported nanoscale zero-valent iron (nanoFe0) composites. However, the effect of BC surface area on the structure, distribution, and performance such as the heavy metal uptake capacity of nanoFe0 particles remains unclear. Soybean stover-based BCs with different surface areas (1.7 − 1 472 m2/g) were prepared in this study. They have been used for in-situ synthesis BCs-supported nanoFe0 particles through carbothermal reduction of ferrous chloride. The BCs-supported nanoFe0 particles were found to be covered with graphene shells and dispersed onto BC surfaces, forming the BC-supported graphene-encapsulated nanoFe0 (BC-G@Fe0) composite. These graphene shells covering the nanoFe0 particles were formed because of gaseous carbon evolved from biomass carbonization reacting with iron oxides/iron salts. Increasing BC surface area decreased the average diameters of nanoFe0 particles, indicating a higher BC surface area alleviated the aggregation of nanoFe0 particles, which resulted in higher heavy metal uptake capacity. At the optimized condition, BC-G@Fe0 composite exhibited uptake capacities of 124.4, 121.8, 254.5, and 48.0 mg/g for Cu2+, Pb2+, Ag+, and As3+, respectively (pH 5, 25 °C). Moreover, the BC-G@Fe0 composite also demonstrated high stability for Cu2+ removal from the fixed-bed continuous flow, in which 1 g of BC-G@Fe0 can work for 120 h in a 4 mg/L Cu2+ flow continually and clean 28.6 L Cu2+ contaminated water. Furthermore, the BC-G@Fe0 composite can effectively immobilize the bioavailable As3+ from the contaminated soil, i.e., 5% (w) of BC-G@Fe0 composite addition can immobilize up to 92.2% bioavailable As3+ from the contaminated soil.